2000
DOI: 10.1046/j.1460-9568.2000.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Galanin‐R1 and ‐R2 receptor mRNA expression during the development of rat brain suggests differential subtype involvement in synaptic transmission and plasticity

Abstract: The present study employed 35S-labelled oligonucleotides and in situ hybridization to examine the distribution in the developing rat brain of mRNA encoding two galanin receptor subtypes, i.e. Gal-R1 and Gal-R2. Gal-R1 and/or Gal-R2 mRNA was detected at embryonic day (E) 20 and from postnatal day (P) 0-70. Gal-R1 mRNA was highly expressed in olfactory regions, ventral hippocampal CA fields, dorsomedial thalamic areas and many hypothalamic nuclei at all ages studied. In adult brain, Gal-R2 mRNA was most abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
102
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 73 publications
17
102
1
Order By: Relevance
“…In the mesencephalon, relatively little GALR1 mRNA has been reported in the rat, except in the superior colliculus, central gray, and (in some studies) the substantia nigra (Burazin et al, 2000;Parker et al, 1995). In contrast, in the mouse we found GALR1 mRNA to be widely distributed throughout the midbrain, suggesting a more important role for galanin in these regions of this species compared with the rat.…”
Section: Distribution Of Galr1 In the Forebrain Of The Mousecontrasting
confidence: 68%
“…In the mesencephalon, relatively little GALR1 mRNA has been reported in the rat, except in the superior colliculus, central gray, and (in some studies) the substantia nigra (Burazin et al, 2000;Parker et al, 1995). In contrast, in the mouse we found GALR1 mRNA to be widely distributed throughout the midbrain, suggesting a more important role for galanin in these regions of this species compared with the rat.…”
Section: Distribution Of Galr1 In the Forebrain Of The Mousecontrasting
confidence: 68%
“…Electrophysiological, behavioral, and neurochemical studies have shown that galanin exerts modulatory (mainly inhibitory) effects on both the noradrenergic and serotonergic systems (Seutin et al, 1989;Sevcik et al, 1993;Pieribone et al, 1995;Xu et al, 1998c;Razani et al, 2001;Kehr et al, 2002;see Ö gren et al, 2006). Moreover, in vivo galanin can modulate 5-HT 1A preand postsynaptic receptor functions in an antagonistic manner (see Fuxe et al, 1998;Misane et al, 1998; The action of galanin is mediated via three G proteincoupled receptors, GalR1-GalR3 (see Branchek et al, 2000), which are expressed in the LC, DR, and their projection areas (Xu et al, 1998b, c;O'Donnell et al, 1999;Burazin et al, 2000;Larm et al, 2003;Hawes and Picciotto, 2004;Hawes et al, 2005;Swanson et al, 2005). Among these receptors, GalR1 and GalR3 mainly activate G i/o types of G proteins mediating inhibitory actions of galanin (Habert-Ortoli et al, 1994;Burgevin et al, 1995;Parker et al, 1995;see Branchek et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There are three galanin receptors, GALR1-GALR3, which all belong to the family of seven transmembrane-spanning, G protein-coupled receptors (26)(27)(28)(29). They are found in many areas of the rat brain, as first shown with autoradiographic ligand-binding methodology (30,31), and later with in situ hybridization (ISH)/quantitative real-time PCR (qPCR) (32)(33)(34)(35)(36). The galanin system has been associated with numerous physiological and pathophysiological functions (29), including depression-and anxiety-like behaviors.…”
mentioning
confidence: 99%